KAJIAN ELEMEN -ELEMEN DESAIN INTERIOR PADA FITNESS CENTER (Studi Kasus : Studi Kasus, FTL Gym Bekasi Timur) - Sofian, Julvi Chairunnas; Melanira, Astria (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
We can interpret the gym as a place or location to carry out exercise and sports activities, suchas gymnastics, athletics and cardio services. It functions as a place for people to exercise andshape their bodies amidst their daily activities. This study aims to analyze the basic elements ofinterior design at Ftl Gym Bekasi. The method used in this study is a qualitative descriptivemethod with stages of analysis based on the basic elements of interior design. This study has theconclusion that the interior design of East Bekasi Ftl Gym is in accordance with existingtheories.